Various estrus-synchronization programs for heifers - Stevenson, Jeffrey S. (Kansas Agricultural Experiment Station and Cooperative Extension Service, 2011)
Various programs of estrus synchronization have been tested during the last 6 years to determine the least costly and most efficacious for dairy heifer replacements. Four systems were tested: 1) a modified Ovsynch treatment (GnRH 7 days before PGF2 alpha followed by GnRH either at 24, 30, 33, 40, or 48 hr, with one fixed-time insemination 16 to 20 hr later); 2) a similar protocol that used GnRH 7 days before PGF [subscript]2alpha followed by insemination at estrus (GnRH + PGF [subscript]2alpha); 3) inseminations after one or two injections of PGF [subscript]2alpha given 14 days apart (PGF [subscript]2alpha; heifers not detected in estrus after the second of two PGF [subscript]2alpha injections were given one fixed-time insemination at 72 hr); and 4) two injections of PGF[subscript]2alpha given 14 days apart followed by GnRH at 33 hr, with one fixed-time insemination 16 to 18 hr later (2 x PGF[subscript]2alpha + GnRH). The PGF[subscript]2alpha treatment in which heifers were inseminated after detected estrus following one or two injections of PGF[subscript]2alpha was the least costly for heifers and produced the best measures of fertility.
Keywords: GnRH; PGF2; Estrus synchronization; Heifers; Dairy